The Influence of Brand Image and Price Discounts on Buying Impulse with Buying Interest as An Intervening Variable: Study of Miniso Consumers in Malang City - Fitrah Muhammad Firdaus; Fani Firmansyah (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
Retail enterprises continue to thrive and evolve, exemplified by specialty shops, convenience stores, and similar establishments. Retail enterprises serve as the final link in the distribution chain, specifically to customers. In particular, brands with a substantial brand image offer discounts to stimulate impulsive customer purchasing. In this instance, consumer impulsive purchases are affected by various factors, including brand perception and discounts. This study aims to assess the direct impact of brand image and discount variables on impulsive purchases and the indirect influence of brand image and discounts on impulsive purchases through the mediation of purchase interest. This research employs a quantitative methodology via a survey approach involving 140 Miniso consumers in Malang City. The study employed online sampling with a questionnaire sent via Google Forms, allowing users to scan a barcode link generated by the researcher, with data analyzed using Smart-PLS 4.0 statistical software. The study's findings demonstrate that brand image significantly influences purchase intention, while discounts also significantly affect purchase intention. However, the brand image only significantly impacts impulse buying. In contrast, discounts significantly influence impulse buying, and purchase intention significantly affects impulse buying. Furthermore, brand image, mediated by purchase intention, significantly impacts impulse buying, as do discounts through purchase intention, specifically among Miniso consumers in Malang City.